The relationship between antecedents of zakat payers' trust and zakat payment channel preferences - Siti Afiqah binti Zainuddin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2014)
Awareness on the immediate need of financial assistance to the poor has been a factor for determining the direct payment of zakat to the eligible party. However, this method of zakat distribution may be ineffective. Zakat can be made more effectively and efficiently managed when paid through a professional zakat institution. This will maximize the assistance rendered to the poor. However, to achieve this, zakat payers' trust and confidence in zakat institutions must be cultivated and maintained. This study examined the perceptions of selected Universiti Malaysia Kelantan's (UMK) staff in Kelantan on the antecedents of zakat payers' trust and its relationship with the attitude (preference) of paying zakat through zakat institutions. The main finding of the study suggests that the antecedents of zakat payers' trust are significantly and positively associated with the payment of zakat through zakat institutions. This indicates that there is a possibility of zakat payers to pay zakat directly to the recipients if they have low level of trust and confidence in zakat institutions. This study helps in ensuring optimal proficiency of zakat institutions and maximization of zakat benefit to the widest possible range of eligible recipients.